The hate u give - Thomas, Angie (London : Walker Books, 2018)
Starr witnesses the fatal shooting of her childhood best friend Khalil at the hands of a police officer. Now, facing pressures from all sides of the community, Starr tries to find her voice in order to stand up for what's right.
Keywords: Witnesses -- Drama; African American teenagers -- Drama; Race relations -- Drama